Private equity investment committee paper on fluidra sa - exit options and returns - Lucas, Luís Miguel De Oliveira (2021)
This Investment Committee Paper was elaborated by a group of students from the Master’s in Finance Program at Nova School of Business and Economics which is intended to be used for academic purposesonly. It consists of an investment proposal for a leveraged buy out on Fluidra SA, a global leader in the Pooland Wellness industry, with aro bust international presence and an extensive portfolio. Operating in both new build and after market sub-sectors, providing high qualitys wimming pool equipment that ranges from above ground and in ground pools to a complete line of accessories and chemical products. The group sought to determine how to be structure an LBO acquisition of Fluidra SA and what returns it could provide, with this work focusing particular lyon studying and assessing the best exit options and expected returns of the transaction.